'The one that got away': how angling as a culture of practice manifests in the teaching and learning relationship within angling-based intervention programmes. Issue 1 (2nd January 2016) - Djohari, Natalie; Brown, Adam; Stolk, Paul
Abstract : In recent years a professional sector has emerged within the UK delivering angling-based intervention programmes targeted at young people 'disengaged' with education. These coaches bring with them an angling cultural background, which influences their interactions with young people as 'novices', emerging in 'angler talk' that accompanies waterside coaching. We argue that young people's exposure to 'angler talk' amounts to a cultural apprenticeship, socialising young people into an experience-based learning community. Through angler anecdotes and waterside banter young people are encouraged to be active participants in an egalitarian system of knowledge exchange that is particularly appealing for working with disaffected young people. By identifying how angling as a community of practice manifests in the teaching and learning relationship, we demonstrate the benefit of ethnographic approaches for appreciating the subtle cultural influences at work in skill-based intervention programmes.